ENT 530 : Case Study: Kittyscarf / Syed Ahmad Muhajir Syed Abdullah ... [et al.] - Syed Abdullah, Syed Ahmad Muhajir; Mohammad Norhan, Nurul Adlina; Mazlan, Muhammad Nur Akashah; Khairulhisyam, Farhah Nabilah; Rohizat, Nurizureen Nazira (2021)
Kittyscarf is an online business which provides various types of scarfs/shawls with simple and minimalist design to their customers. This business offers affordable products with high quality to their customers by giving a price cut if they buy more than one item based on material and types of seams. Its simplicity and minimalistic product design enhances the flexibility of product on styles applicable to wear fashionized suit for each person. Kittyscarf target audience are teen adult Muslim ladies who look for scarf with simple and flexible design nevertheless still contain elegance. Due to the increase in trend on various shawl styles, Kittyscarf also targeting ladies who are influenced by the trend and as it has simple design, kittyscarf believe it will be applicable for a long period. One of the main business problems is the nature of its business. As hijab is one of the main appearances etiquette for Malaysian Muslim women, there are many competitors in the Malaysia hijab fashion industry and the inflow of new entrepreneurs in this sector are overwhelming and did not showing any sign of decreasing. By fully utilizing online platform, Kittyscarf would be able to attract more customers. A creative usage of social media and online marketing tools will outshine its competitors as the marketing will allow the name of Kittyscarf being seeded in the mind of the online shoper.